2021
DOI: 10.37897/rmj.2021.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Depression in Mothers and Fathers – An Underestimated Diagnosis

Abstract: Postpartum depression remains a significant healthcare priority due to the social and family consequences. Research has shown that both mothers and fathers experience significant psychological changes during pregnancy and postnatally, including depressive disorders. Underdiagnosed in most cases, the short and long-term consequences involve infant and child development, family’s life and social disruption. Because this pathology may lead to deviation from behavioural and social norms, we want to emphasize that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The COVID-19 pandemic and its related restrictions have led to important changes in people's daily lives to limit its rapid spread worldwide, severely affecting the mental health of new mothers and fathers [12,14,25]. Epidemiological studies that systematically assessed the impact of COVID-19 on parents during the postnatal period have underlined a dramatic increase in the rates of prevalence of PND among mothers [36,37] and fathers [43,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic and its related restrictions have led to important changes in people's daily lives to limit its rapid spread worldwide, severely affecting the mental health of new mothers and fathers [12,14,25]. Epidemiological studies that systematically assessed the impact of COVID-19 on parents during the postnatal period have underlined a dramatic increase in the rates of prevalence of PND among mothers [36,37] and fathers [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, for fathers, the birth of a child entails major transformations related to the necessity of adapting to the child's new rhythms and needs, and having to redefine one's relationships and self-identity, which may be associated with increased levels of stress, anxiety, and depression [10]. In this context, the COVID-19 outbreak and its related restrictions, resulting in a worldwide traumatic experience [11], posed an additional risk to the mental health of postpartum women and men who were shown to be one of the high-risk group populations for negative effects of the pandemic on psychological well-being [12][13][14]. Even before the advent of the COVID-19 pandemic, studies conducted during previous natural disasters had shown higher rates of psychiatric disorders among perinatal women with respect to the general population [15].…”
Section: Introductionmentioning
confidence: 99%